DAMPAK PEREKONOMIAN GLOBAL TERHADAP KONDISI MAKROEKONOMI INDONESIA - Nurhidajat, R. (Badan kebijakan Fiskal, 2010)
The purpose of this paper is to provide an analysis of relationship between global economy represented by US economy and Indonesia's economy by quarterly data. In this paper, domestic variables are Gross Domestic product (GDP), intersest rate, composite price index and exchange rate. Meanwhile, The global variables used are Gross Domestic product (GDP), intersest rate, and composite price index. Struktural VAR is employed to test these relationship. The quarterly data are between 1999 through 2008. The result of this reseach is Indonesia as a small open economy is influenced by global economy. The Government of Indonesia should give more attention to US GDP as the most influent variable of international variables.